SPE EUROPEC/EAGE Annual Conference and Exhibition 2010
DOI: 10.2118/130388-ms
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Oil Recovery Limit in Malaysian Thin Oil Rim Reservoirs: Force Balance Revisited

Abstract: The goal of an oil field development project is to accelerate the hydrocarbon production and optimize the recovery at the lowest cost. For a thin oil rim reservoir with a large gas cap on top and a strong aquifer below, achieving such goal can be very challenging since recovery of both oil and gas needs to be optimized. A successful project may entail plan first to accelerate the oil production with re-injection of the produced gas at the gas cap, maximizing the oil recovery prior to the start-up of the gas ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…For the subject reservoir, it had been studied and discussed (Ref. 3). It was concluded that the art of maximizing oil recovery of a thin oil rim reservoir is to keep oil rim in contact with producing wells at all time and that this could be achieved by balancing the WOC and GOC movement by controlling produced gas injection in the gas cap.…”
Section: Force Balance In Thin Oil Rim Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the subject reservoir, it had been studied and discussed (Ref. 3). It was concluded that the art of maximizing oil recovery of a thin oil rim reservoir is to keep oil rim in contact with producing wells at all time and that this could be achieved by balancing the WOC and GOC movement by controlling produced gas injection in the gas cap.…”
Section: Force Balance In Thin Oil Rim Reservoirsmentioning
confidence: 99%
“…During this oil rim oil production period, the Gas Injection/Gas Production ratio (GIGP) has to be kept at high values although it depends on aquifer strength and fluid production (viscous withdraw) volume and rate (Ref. 3). …”
Section: Early Gas Production For Salesmentioning
confidence: 99%
“…In a study on production optimization, Hasan et al (2009) indicated a significant increase in oil recovery factors in an oil rim reservoir when a binary integer programming, a production optimization technique was used to determine the choke and rate settings in production and injection wells. Razak et al (2010) reported improved oil recovery factors (by 35-48%, which is higher than the theoretical recovery efficiency) in their work by understanding water and gas coning tendencies in thin oil rim reservoirs. They highlighted the impact of force balance changes (coning tendency) by increasing the viscous withdrawal with the use of horizontal wells, coupled with gas re-injection to obtain higher recovery efficiency.…”
Section: Introductionmentioning
confidence: 97%
“…When using ordinary directional wells for development, the energy in the gas area and the marginal water area is bigger than the energy in the oil ring. During the exploitation process, the top natural gas and the marginal water are driven by the formation pressure difference [2]. These development characteristics lead to the characteristics of rapid growth in the early development phase and a short water-free recovery period for gas caps and marginal water reservoirs.…”
Section: Introductionmentioning
confidence: 99%